Right Ventricular Dysfunction and Exercise Impairment in Patients with Heart Failure, Insulin Resistance, and Diabetes Mellitus: Insights from the T.O.S.CA. Registry (Cardiovascular Diabetology 2022) - Triggiani, Domenico; Lisco, Giuseppe (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: Insulin resistance (IR) and type 2 diabetes mellitus (T2D) are known to affect the progression of chronic heart failure (CHF), but little evidence exists about the impact of IR and T2D on right ventricular dysfunction and exercise tolerance. Insights from the T.O.S.C.A. Registry: Echocardiographic hallmarks and cardiopulmonary exercise test (CPET) results were evaluated at baseline and after an average time of 36 months. T2D patients exhibited a greater intraventricular septum (IVS) thickness (11 ± 2 mm, 10 ± 2 mm, 10 ± 2 mm, in T2D, IR, and EU, respectively; p<.05) and LV wall thickness (0.34 ± 0.1, 0.32 ± 0.1, and 0.32 ± 0.1, in T2D, IR, and EU, respectively; p<.05). Moreover, T2D patients exhibited worse LV filling dynamics with larger left atrial volume index compared to IR and EU. Right ventricle dysfunction, expressed as a lower TAPSE/PASP ratio, was found in T2D [0.52(0.32–0.72)] than in EU and IR [0.60(0.30–0.90); p<.05]. T2D patients showed a significantly lower VO2 max peak when compared to IR and EU patients (15.8 ± 3.8 vs. 16.5 ± 4.3 vs. 18.4 ± 4.3 ml/Kg/min; p<.003), with an inverse relationship between the HOMAIR classes and VO2 max. Right ventricle structure and function deteriorated more rapidly in T2D, as suggested by more relevant deterioration in TAPSE/PASP ratio (-10% in EU patients, -14% in IR patients, -21% in T2D; p<.05). Commentary: The study findings suggest that the right ventricle structure, function, and cardiopulmonary performance deteriorate with IR and, more evidently, due to chronic exposure to hyperglycemia in T2D. Impaired exercise tolerance, poor cardiorespiratory fitness, diastolic dysfunction, and left atrial enlargement predispose patients to poor quality of life, suboptimal adherence to physical activity, and an overall increase in the risk of all-cause and cardiovascular mortality. In addition, chronic hyperglycemia accelerates the progression of these alterations, especially in patients with poor glycemic control over time. Highly selective and even more non-selective sodium glucose transporter type 2 inhibitors and glucagon-like peptide 1 receptor agonists should be considered as the first-line therapy for improving CV outcomes in T2D and CHF. Further studies are needed to understand the role of these molecules in treating pre-clinical conditions, such as IR and metabolic syndrome.
Keywords: right ventricle dynamics